Developmental stages of a mottled emigrant butterfly, catopsilia pyranthe - Arju, MH; Bashar, MA; Moula, G (Dhaka University Journal of Biological Sciences, 2011)
The overall life cycle, duration and survival rate of different developmental stages (egg, larva and pupa) of Catopsilia pyranthe conducted at 27 ± 3°C and RH 75% ± 2. showed that within 6.4 days 68% eggs hatched. The average duration from egg to adult, larval stage and pupal were 23.87, 10.93 and 6.8 days, respectively. Fifty six out of 68 larvae successfully completed their whole 5 instars. There were positive correlation among the larval instars, amount of food consumption and excretion of faeces. About 52% pupa were emerged as adult at laboratory condition. Key words: Life cycle; Catopsilia pyranthe; Developmental stages; Rearing DOI: http://dx.doi.org/10.3329/dujbs.v19i2.8961 DUJBS 2010; 19(2): 171-179